2018
DOI: 10.1002/tox.22579
|View full text |Cite
|
Sign up to set email alerts
|

Coronarin D induces apoptotic cell death through the JNK pathway in human hepatocellular carcinoma

Abstract: Coronarin D, a diterpene derived from the rhizomes of Hedychium coronarium, has been used to treat inflammatory diseases. Coronarin D can exert strong anticancer effects through cell growth prevention and cell cycle arrest in many cancer cells. In this study, we investigated the molecular mechanism through which coronarin D suppresses cell proliferation and triggers cell death in human hepatocellular carcinoma (HCC) cells. Treatment of Huh7 and Sk-hep-1 cells with coronarin D resulted in a significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…Apoptosis is a molecularly programmed cell death with the key elements of death receptors, membrane alterations, protease cascade, mitochondrial changes, and DNA fragmentation . Consistent with other research that has been conducted on CD, our results also showed that CD induced cell G2/M arrest, and altered the mitochondrial membrane potential, all of them involving apoptosis (Figures ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Apoptosis is a molecularly programmed cell death with the key elements of death receptors, membrane alterations, protease cascade, mitochondrial changes, and DNA fragmentation . Consistent with other research that has been conducted on CD, our results also showed that CD induced cell G2/M arrest, and altered the mitochondrial membrane potential, all of them involving apoptosis (Figures ).…”
Section: Discussionsupporting
confidence: 91%
“…Coronarin D derived from the roots of Hedychium coronarium , exhibits promising anti‐proliferative, pro‐apoptotic, anti‐invasive, and anti‐angiogenetic effects and is a potential natural anti‐cancer agent for nasopharyngeal carcinoma and human hepatocellular carcinoma . However, the definite effects of CD against human oral cancer are uncertain currently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many natural products can suppress proliferation by arresting cells at phases in the cell cycle [25]. The p21 is a small protein with 165 amino acids and belongs to the CIP/Kip family of CDK inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Coronarin D exhibits antiproliferative, pro-apoptotic, anti-invasive, antiangiogenic, antiosteoclast, and anti-inflammatory activity by suppressing NF-κB and the gene products regulated by this pathway of osteoclastogenesis [24]. Recently, Coronarin D has been described as inducing apoptosis in human hepatocellular carcinoma (HCC) [25] and in human oral cancer (OSCC) [26] through the c-Jun N-terminal kinases (JNK) pathway while it has induced reactive oxygen species-mediated cell death in human nasopharyngeal cancer cells (NPC) through inhibition of p38 mitogen-activated protein kinase (MAPK) and activation of JNK [27].…”
Section: Introductionmentioning
confidence: 99%